Polyethylenimine-functionalized mesoporous silica-chitosan composites and their ability to adsorb Pb(ii). (21st November 2022) - Cui, Junshuo; Guo, Liangyu; Wang, Dandan; Chen, Xia; Lou, Zhenning; Shan, Weijun; Xiong, Ying
Abstract : A mesoporous adsorbent was synthesized within a short time by a microwave-assisted method, and it showed high capacity and reusability for Pb(ii ) adsorption. Abstract : There is an urgent need to reduce heavy metal contamination of the environment because the ions can accumulate in living organisms, yet the lack of highly efficient and cost-effective treatment methods remains. In this study, polyethylenimine (PEI)-functionalized mesoporous silica–chitosan composites were synthesized via a microwave-assisted method, and it was applied for the removal of Pb(ii ). Inexpensive sodium silicate and chitosan were chosen as precursors to construct a basic mesoporous silica–chitosan skeleton. Epichlorohydrin (ECH) was used to further cross-link PEI molecules onto the porous substrate. PEI played a critical role in the adsorption of Pb(ii ) and was beneficial because its multiple N atoms coordinated with the metal ions. The adsorbent CK-T50 /t20 -m0.2 exhibited the strongest adsorption performance, of which the capacity for Pb(ii ) reached 279.08 mg g −1 . After six adsorption–desorption cycles, the capacity was preserved at 94.7%, and the regeneration rate reached 93%, demonstrating its satisfactory stability and cyclic performance. The effect of pH, adsorption kinetics, adsorption isotherms, and thermodynamics of the process were also studied. The adsorbent is a promising material for use in practical applications of heavy metal removal.